Incidence of sleep bruxism among children in Itanhandu, Brazil - Esteves Fonseca, Carina Magalhaes; Fernandes dos Santos, Mateus Bertolini; Xediek Consani, Rafael Leonardo; Fernandes dos Santos, Jarbas Francisco; Marchini, Leonardo [UNESP] (Springer Heidelberg, 2011)
Sleep bruxism (SB) in children may be related to headaches and causes extensive damage of primary teeth. This paper evaluates the incidence of SB in children from Itanhandu, MG, Brazil.The presence of teeth wear facets was verified through clinical examinations on a sample of children, whose parents answered a questionnaire about their children's behavior and habits. Analysis of variance and chi-square tests (p = 0.05) were applied to identify possible correlations between the presence of SB and the parents' responses to the questionnaire.The sample comprised of 170 children, 51.76% (n = 88) of which were girls, while the average age was 4.37 (+/- 1.69) years. A total of 15.29% (n = 26) had been diagnosed as bruxers, 46.47% displayed restless behavior, and only 10% used medication. The average duration of breastfeeding was 4.4 (+/- 0.25) months. A positive correlation was found between restless behavior and the presence of SB (p < 0.001). No correlation was found between SB and medication (p = 0.573), or between the duration of breastfeeding and restless behavior (p = 0.102), SB (p = 0.565) and medication (p = 0.794).Restless behavior was positively correlated with SB, although no correlation was found between SB and medication or duration of breastfeeding.
Keywords: Sleep bruxism; Children; Breast feeding; Temporomandibular joint dysfunction